POWER, HOMOSEXUALITY AND OLD AGE:: TRANSGRESSIONS AND SILENCES UNDER THE REPRESENTATION OF TARGET DUMBLEDORE - Cardizi, Gabriella (Revista Gênero e Interdisciplinaridade, 2021)
The present work will use a political perspective that circumscribes the character Alvo Dumbledore, created by the writer J. K. Rowling in the literary and cinematographic fields of Harry Potter. Here, the attempt to understand the way in which characteristics that come and go with various aspects of common sense about what is expected of a figure of power are concentrated in such a character. Drawing on the professional and personal spheres, Dumbledore will meet socially constructed expectations about masculinity1; in addition, it will use the way the character is constructed in contrast to the way it is represented, that is, there is another parity of confrontation: in the magical environment of its own universe and in the cinematographic environment, as far as the film industry is concerned. and public acceptance.